Pengaruh Growth EBit Terhadap Intrinsic Value Dan Price Earning Ratio - Muktiadji, Nusa; Tjandrawan, Denny Iskandar (Ilmiah Manajemen Bisnis, 2014)
ABSTRACTThe Purpose of financial management is to maximalize wealthness of shareholders with improving companies value includes intrinsic value and market value. To reach the target of financial management with improving revenue. On improved revenue every years mean that company profit growth experience. When company have increase profit growth the intrinsic value and market value will be increase too. Analysis method is about relation between variable and this research using coefisien correlation (r) and simple regression linier (ÃÂ²). The purpose of this research is to know about relation between profit growth (X) using growth of EBIT every years toward growth of intrinsic value using earning multiplier method and growth of market value using price earning ratio. Research periods that is started in 2006 until 2011, with take two sample used companies, they were PT Indofood Sukses Makmur, Tbk and PT Mayora Indah, Tbk. This research established that using coefisien correlation (r), profit growth toward intrinsic value growth have a forceful relation are 0,787, and in simple regression linier obtain equation Y1 = 0,166 + 0,255X that showed profit growth toward market value growth that using coefisien correlation (r) have a very low relation are 0,190 and in simple regression linier obtain equation Y2 = 0,176 + (-0,575)X that showed profit growth have negative influence toward market value growth in PT Indofood Sukses Makmur, Tbk. All in the same with PT Mayora Indah, Tbk that using coefisien correlation (r), profit growth toward market value growth, have a low relation are 0,207 but in simple regression linier obtain equation Y2 = 0,099 + 0,502X that showed profit growth have positive influence toward market value growth. The result research showed that profit growth have a relation toward intrinsic value growth and market value growth but negative influence in PT Indofood Sukses Makmur, Tbk and positive influence in PT Mayora Indah, Tbk.Keywords: Profit Growth, Intrinsic Value Growth and Market Value Growth